2014
DOI: 10.1007/5584_2014_22
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Immunoprophylaxis in Suppressing Carriage of Neisseria Meningitidis in the Military Environment

Abstract: Neisseria meningitidis, etiological factor of invasive meningococcal disease, is a human commensal that colonizes the nasopharynx. Colonization is usually asymptomatic, but it is a prerequisite for disease. Asymptomatic carriers are the major source of infection. In the present study, a survey of N. meningitidis carriage was conducted between January and March 2013 in a military unit in Poland. Single-time throat culture samples were collected from professional 559 soldiers (302 unvaccinated vs. 257 vaccinated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…This study identified a carriage prevalence of 16% for N. meningitidis in those entering a military college in the Russian Federation, and similar rates have been seen in recruits entering a military setting in Greece (15%) (Tryfinopoulou et al, 2016) and Poland (16-24%) (Tyski et al, 2001), with lower carriage rates seen for recruits entering a military setting in Turkey (4.2%) (Celal Basustaoglu et al, 2011) and Iran (8%) (Ataee et al, 2016) and professional soldiers in Poland (5.2% and 9.6%) (Korzeniewski et al, 2017;Korzeniewski et al, 2015). It was anticipated that the carriage rate would increase after recruitment while the recruits resided in a semi-closed environment as these populations are at higher risk for outbreaks of meningococcal disease (Aguilera et al, 2002;Brundage et al, 2002; National Foundation for Infectious Diseases (NFID), 2017); while a study of the change in carriage rate in students identified a rapid increase on entering university (Neal et al, 2000).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…This study identified a carriage prevalence of 16% for N. meningitidis in those entering a military college in the Russian Federation, and similar rates have been seen in recruits entering a military setting in Greece (15%) (Tryfinopoulou et al, 2016) and Poland (16-24%) (Tyski et al, 2001), with lower carriage rates seen for recruits entering a military setting in Turkey (4.2%) (Celal Basustaoglu et al, 2011) and Iran (8%) (Ataee et al, 2016) and professional soldiers in Poland (5.2% and 9.6%) (Korzeniewski et al, 2017;Korzeniewski et al, 2015). It was anticipated that the carriage rate would increase after recruitment while the recruits resided in a semi-closed environment as these populations are at higher risk for outbreaks of meningococcal disease (Aguilera et al, 2002;Brundage et al, 2002; National Foundation for Infectious Diseases (NFID), 2017); while a study of the change in carriage rate in students identified a rapid increase on entering university (Neal et al, 2000).…”
Section: Discussionmentioning
confidence: 64%
“…This study was also only conducted at 3 time points and was not a continuous longitudinal sampling study, and so provides only a limited understanding of the dynamics of carriage changes in this population, and cannot provide information on transmission patterns. Additionally, many of the isolates were ungroupable, which has been seen before in carrier studies (Caugant et al, 2006;Celal Basustaoglu et al, 2011;Glitza et al, 2008;Korzeniewski et al, 2015;Tyski et al, 2001) and previous evidence has shown challenges in serogrouping of isolates from carriage studies due to reduced or no capsule expression in the carriage state (Jones et al, 2016). Similarly genetic plasticity of the capsule can effect PCR assay sensitivity (Jones et al, 2016) and may have resulted in some of the discrepancy seen between the assays.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Introduction of the MenC monovalent conjugate vaccines previously reduced carriage acquisition of MenC strains in adolescents and young adults ( 9 ). There is evidence, albeit limited, to suggest that the quadrivalent vaccine may have a similar effect on carriage of MenCWY strains ( 10 , 11 ). Reduced carriage in this population should lead to indirect protection of other age groups through herd immunity, thus enhancing the public health effect and cost-effectiveness of this approach.…”
mentioning
confidence: 99%
“…In Poland, there have been reports of IMD cases in recent years; however, the actual carriage incidence of N. meningitidis among Polish residents has not been determined (Jafri et al 2013). Many of Polish and European publications on the N. meningitidis carriage incidence are limited to military environment (Chapalain et al 1992;Tyski et al 2000;Korzeniewski et al 2015). According to the research findings, meningococcal carriage is high among conscripted soldiers serving in European armies, whereas among profes-sional soldiers it was found to be like the carriage rates observed in the general population (Korzeniewski et al 2017).…”
Section: Discussionmentioning
confidence: 80%